Development of novel extraction techniques for the determination of polycyclic aromatic hydrocarbons in wastewater and sludge - Ncube, Somandla (My University, 2018)
This thesis presents development, optimization and application of two novel extraction techniques for the determination of total polycyclic aromatic hydrocarbons in wastewater and wastewater sludge. PAHs belong to an important class of persistent organic pollutants that are commonly found in the environment at low concentrations. The sources of these compounds include anthropogenic activities such as chemical industries, combustion and agriculture activities. Owing to their potential carcinogenicity, mutagenicity and teratogenicity, it is important to determine polycyclic aromatic hydrocarbons in several matrices, particularly complex ones such as wastewater and wastewater sludge. To date, very few studies have looked at the detailed presence and distribution of these compounds within wastewater and wastewater sludge in South Africa and internationally. Although the official methods approved by international bodies like the US-EPA are able to extract polycyclic aromatic hydrocarbons in wastewater sludge, all of them involve two separate steps. The steps generally include extraction of the target compounds along with other unwanted compounds followed by the cleanup step before analysis. A two-step approach increases the errors in measurements and it is time consuming. Therefore, the primary goal of this study was to develop, optimize and validate novel extraction techniques for selective extraction of polycyclic aromatic hydrocarbons from wastewater and wastewater sludge. The novelty of these techniques is that they combine two or three extraction steps into one thereby minimizing sample turnaround time and method errors that might arise due to non-ideal analytical behaviour of the setup. The first part of the work involved synthesis and characterization of a molecularly imprinted polymer that would enhance selectivity of extraction of polycyclic aromatic hydrocarbons. Several other adsorbents in the analysis of polycyclic aromatic hydrocarbons have been reported by different researchers. These were presented in this thesis as a review article (Paper 1). Key in the synthesis of the polymer was the choice of the appropriate template that could create cavities with vii an affinity for all the 16 US-EPA priority polycyclic aromatic hydrocarbons. Several cavity-tuning experiments were done to find the best imprinted polymer. A polymer combination consisting of benzo[k]fluoranthene-imprinted and indeno[1 2 3-cd]pyrene-imprinted polymers mixed at 1:1 (w/w) was successfully screened from these experiments. The polymer mixture showed high selectivity and affinity towards all 16 US-EPA priority polycyclic aromatic hydrocarbons. This work is presented as Paper 2. The average extraction efficiency from an aqueous solution was 65 ± 13.3% (n = 16, SD). The maximum binding capacity of the polymer was 5.19 ± 0.392 mg g-1 (n = 3, SD) with binding capacities of individual polycyclic aromatic hydrocarbon ranging from 200.8 - 493.9 μg g-1. Batch adsorption and kinetic studies confirmed that the binding of polycyclic aromatic hydrocarbons onto the molecularly imprinted polymer particles resulted in formation of a monolayer and that the binding process was the rate limiting step. The molecularly imprinted polymer performance studies confirmed that the synthesized polymer had an imprinting efficiency of 103.9 ± 3.91% (n = 3, SD). A comparison of the theoretical number of cavities and the experimental binding capacity showed that the overall extent of occupation of the imprinted cavities in the presence of excess polycyclic aromatic hydrocarbons was 128 ± 6.45% (n = 3, SD). The loss of selectivity was estimated at 2.9% with every elution cycle indicating that the polymer can be re-used several times with limited loss of selectivity and sensitivity. The polymer combination was proven to be an effective adsorbent that can be used to isolate all 16 US-EPA priority polycyclic aromatic hydrocarbons in solution. The combined molecularly imprinted polymer particles were then used to selectively extract the 16 US-EPA priority polycyclic aromatic hydrocarbons during development of two novel techniques for the analysis of these pollutants in wastewater and wastewater sludge. The polymer combination was first used during development of a novel extraction technique referred to as the membrane assisted solvent extraction-molecularly imprinted polymer (MASE-MIP) technique. The approach was to place the MIP particles in a microporous membrane bag of 0.22 µm pore size, 160 µm thickness and 15 mL internal viii volume. This work is presented as Paper 3. The optimised conditions for the twoway MASE-MIP technique were found to be 25% of dimethyl sulfoxideas an organic modifier in the aqueous sample, 80 mg of MIP particles in the membrane bag, 180 min extraction time and 1000 rpm stirring rate. The extraction efficiency for this combination ranged between 61.2 and 96.8% with an average of 77.4% for all 16 polycyclic aromatic hydrocarbons and a method detection limit ranging between 0.01 and 0.45 ng mL-1. This developed technique showed remarkable selectivity and extraction capability for the polycyclic aromatic hydrocarbons soluble in wastewater. The MASE-MIP technique was further combined with Soxhlet extraction to form a three-way extraction technique referred to as the Soxhlet extraction-membrane assisted solvent extraction-molecularly imprinted polymer (SE-MASE-MIP) technique (Paper 4). The SE-MASE-MIP technique combines the extraction efficiency of the Soxhlet extractor, the selectivity of a size exclusion membrane and the specificity of a molecularly imprinted polymer into a single stem format for the extraction of polycyclic aromatic hydrocarbons from wastewater sludge. This technique was optimised for various parameters such as extraction solvent, reflux time and membrane acceptor phase. The developed technique was optimised using a wastewater sludge certified reference material and then tested on real wastewater sludge samples. The extraction efficiencies of the 16 US-EPA polycyclic aromatic hydrocarbons from wastewater sludge samples using the developed technique ranged from 17 to 48% with %RSD values ranging from 0.78 to 18%. The method detection limits ranged from 0.14 to 12.86 ng g-1. Thus, despite relatively low extraction efficiencies, the extraction process was reproducible and showed remarkable selectivity. The developed technique is a promising prospect that can be applied in the analysis of organic pollutants from complex solid samples. In this case, extraction of PAHs from Soxhlet was found to be the rate limiting factor. The impact of the MASE-MIP and the SE-MASE-MIP techniques was demonstrated in the clean chromatographic patterns generated for both certified reference materials and real samples, indicating an effective removal of impurities ix (interferences) for final chromatographic instrumental analysis. The two developed techniques were therefore considered quite novel and innovative for handling complex matrices such as wastewater sludge, where current approved standard methods are still affected by matrix effects and the existence of target compounds in the nano-scale.
A thesis submitted to the Faculty of Science, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy, 2018
Keywords: Aromatic compounds--Synthesis; Polycyclic aromatic compounds